Experimental and analytical investigations of reinforced concrete beams strengthened by different CFRP sheet schemes. (Fracture and Structural Integrity, 2021)
The use of bonded externally polymer reinforced fiber (FRP) Laminates has been introduced as an effective approach in rehabilitating (RC) structures due to their high strength, corrosion resistance, reduced weight, and ease of use. This paper discusses the experimental results of the flexural reinforcement of RC beams by CFRP sheets bonded by epoxy adhesive to the tensile surface of the beams. Using a four-point bending load system over an effective clear length of 1800 mm, a total of ten beams with an overall dimension of 150 * 200 * 2000 with different degrees of strengthening schemes were constructed and tested. A numerical study using ANSYS finite element program was conducted by modeling RC beams. The number of layers, strengthening scheme (side and U-shape bonding) and reinforcement ratio are the major parameters of the experimental study. the research indicate that the flexural strength of the beams was substantially improved as the layers of laminate increased between 31.80 and 71.50 % and using U shape in ends delaying or preventing debonding failure. The result obtained using ANSYS model showed acceptable agreement with the experimental results, with deviations varying no more than 10 % for all specimens.
Keywords: Strengthening; Carbon fibre reinforced polymer; Deflection; ANSYS; Ultimate strength; Ductility